Evaluación Taxonómica de Especies Forestales Pioneras y su Valor Ambiental en el Área Recuperada del Centro de Producción e Investigación Pabloyacu, Moyobamba 2012 - Parodi Ramirez, Yuri Gary (2013)
This thesis "Taxonomy Species Pioneer Forest Assessment and Environmental Value of Reclaimed Area and Production Center Pabloyacu Research Moyobamba 2012" aims to contribute to research concerning the pioneer species colonizing degraded areas and recuperative function in comparative with the introduced and invasive species. For this purpose the recovery area in the Production Center and Research Pabloyacu was chosen, this area is 0.84 hectares and is being recovered from about 10 years for students and teachers. Was chosen for this study design or systematic sampling transects belts (Malleux 1982), and 05 transects of 24 x 35 mt. were established, where information dasometric height (h) , diameter (d) and number of species by common name was recorded. Structural variables of abundance (RA), dominance (DR), frequency (FR) and Importance Value Index (IVI) and estimating the Margalef richness index (DMg) were determined. 17 families distributed in 22 genera and 22 species were recorded. The family produces the highest species richness was Fabaceae, with 04 species. Species or plant community consists primarily studied species “Huarmi huarmi” (Didymopanax morototoni) with 50 registered plant, “Machete vaina” (Bauhinia longifolia) with 36 registered plants, “Sacha shimbillo” (Macrolobium limbatum) with 12 registered plants and “Cetico” (Cecropia sp ) 4 registered plants, whose respective importance value indices were 20.21 % , 30.51 % , 6.41 % and 12.66 % , respectively, for those who also value wealth index DMg 9.5 , 6.8 , 2.1 and 3.3 respectively recorded .